Nyctomyia biunguiculata, a new cavernicolous species of tribe Aedini (Diptera: Culicidae) from southern Thailand - Harbach, Ralph E.; Taai, Kritsana (Zootaxa, 2014)
Nyctomyia biunguiculata, sp. n., is described from a unique male reared from a pupa (exuviae partially decomposed and over cleared) collected from a rimstone pool deep inside Wat Sumano cave located in Phatthalung Province of southern Thailand. The genitalia of the holotype are illustrated, and the species is compared with Nc. pholeocola, the type species of the genus described from a cave in another province of southern Thailand. The species has not been found outside the cave and appears to be a true troglobite.